2012
DOI: 10.1021/la302792z
|View full text |Cite
|
Sign up to set email alerts
|

Site-Dependent Donation/Backdonation Charge Transfer at the CoPc/Ag(111) Interface

Abstract: The organic/metal interface formed upon adsorption of cobalt(II) phthalocyanine (CoPc) molecules on a flat Ag(111) single crystal was investigated using a combination of scanning tunneling microscopy (STM) and photoemission spectroscopy (PES). A flat-lying molecular adsorption with the π conjugated phthalocyanine ligand parallel to the substrate was found to lead to an effective molecule-substrate coupling which governs a template-guided molecular growth. A voltage polarity dependence at the cobalt ion site wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 38 publications
6
37
0
Order By: Relevance
“…The model for the line-shape analysis we have used is shown in red and blue color coding for PTCDA and CuPc carbon species, respectively. It is based on own high-resolution and high-statistics XPS measurements and in good agreement with models from literature [3,[64][65][66][67]. The best fits are shown as green lines.…”
Section: Vertical Structuresupporting
confidence: 74%
“…The model for the line-shape analysis we have used is shown in red and blue color coding for PTCDA and CuPc carbon species, respectively. It is based on own high-resolution and high-statistics XPS measurements and in good agreement with models from literature [3,[64][65][66][67]. The best fits are shown as green lines.…”
Section: Vertical Structuresupporting
confidence: 74%
“…Valence band photoemission spectra in the submonolayer range showed two signals at 1.0 and 1.4 eV below E F (see Fig. 39) [249,571], which closely resembled the peak structure predicted for CoPc/Ag(1 1 1) [248], although the absolute peak positions differed from the predictions. The same signal structure was found for CoPc on Ag(1 0 0) [250].…”
Section: Cobalt Complexessupporting
confidence: 66%
“…Instead, the major signal contributions were shifted to lower binding energies and the multiplet structure vanished. The 2p 3/2 and 2p 1/2 components shifted by 1.8 eV and 2.7 eV, which reduced the spinorbit splitting from 15.7 to 14.8 eV [249,571] and thus led to a spectrum characteristic of diamagnetic S=0 cobalt compounds and Co metal. It has been concluded that the Co(II) metal center is reduced by electrons from the Ag substrate [249,571].…”
Section: Cobalt Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…Changing interfacial electronic structure well below the frontier orbitals introduces one final point: Hybridization with the surface occurs not only near E F , but also for lower-energy states. These lower-lying orbitals are often overlooked, but may provide a pathway for charge backdonation to offset the extent of charge transfer accompanying f -LUMO formation [55,56].…”
Section: Discussionmentioning
confidence: 99%